LINGUOCOGNITIVE FEATURES OF CONTEXTUAL ANTONYMS IN THE ENGLISH AND UZBEK LANGUAGES - Usmonov Shohsulton (TADQIQOTLAR, 2026)
Abstract: The present article investigates the linguocognitive features of contextual antonyms in the English and Uzbek languages from a comparative and interdisciplinary perspective. Unlike conventional lexical antonyms, which are fixed and systemically encoded in the language, contextual antonyms emerge dynamically within discourse as a result of cognitive operations, pragmatic intentions, and situational constraints. The study is grounded in the theoretical frameworks of cognitive linguistics, linguoculturology, and discourse analysis, viewing language as a reflection of human conceptualization and mental categorization of reality. In this regard, contextual antonymy is interpreted not merely as a semantic opposition, but as a cognitively motivated mechanism through which speakers conceptualize contrast, evaluation, and categorization in context. The research aims to identify the cognitive principles that underlie the formation and interpretation of contextual antonyms in English and Uzbek, and to reveal both universal and language-specific features of this phenomenon. Particular attention is paid to such linguocognitive mechanisms as conceptual opposition, profiling and backgrounding, metaphorical and metonymic mapping, scalar evaluation, and frame-based interpretation. The analysis demonstrates that contextual antonyms are often activated through shared background knowledge, cultural models, and pragmatic inferences, rather than through direct lexical opposition. As a result, the recognition of antonymic relations depends heavily on discourse context and the interlocutors’ cognitive competence.